Farm differentiation and intervention targeting in Mixed Farming Systems of Coastal and Inland Bangladesh - Mponela, Powell; Ahmed, Sharif; Farah Deba Keya; Ishrat Jahanara; Masud Rana; Lopez-Ridaura, Santiago; Krupnik, Timothy J. (International Maize and Wheat Improvement Center, 2025)
Multiple stakeholders use farm and farmer attributes such as land size and experience to select participants and beneficiaries for agricultural interventions. Such criterion often ensures project success and impact but potentially widens inequality if uncoordinated. In South Asia, despite the general improvement in farm productivity, not all farmers have benefited and wide variability in performance persist. Over past decades, vertical research-extension-farmer innovation transfer approaches have evolved to enable increased and direct interactions among researchers, extension, private sector and farmers. Horizontal participatory approaches have facilitated co-creation and codesign of interventions tailored to specific farmer segments. This study demonstrates how participatory workshops can be used to segment different farm typologies and design targeted strategies. Bangladesh is used as a cast study example for diverse intensification strategies due to regional variations in cropping systems driven by environmental and resource constraints. In the South, farmers are often limited to single-season rice cultivation due to flooding, salinity, irrigation, and land tenure challenges while in the North, diverse cropping patterns are enabled by better resource access and stronger markets. Using the approaches described in this report, organizations can design interventions to address specific regional challenges, such as soil quality issues in the North and salinity problems in the South. Economic conditions can dictate cropping intensity: limited finances may constrain farmers in southern Bangladesh, while those in the north can optimize crop choices for better returns. This study provides a methodological approach that can enhance innovation targeting given these differing circumstances by combining broad strategies for wide adoption with tailored approaches for specific farmer segments. While generalized strategies may enable mass adoption, they also have negatives, namely that they can overlook local variations and potentially worsen inequalities, highlighting the need for coordinated efforts to meet the diverse needs of farming communities.